The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/nu11092061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice, Wheat, and Mung Bean Ingestion on Intestinal Gas Production and Postprandial Gastrointestinal Symptoms in Non-Constipation Irritable Bowel Syndrome Patients

Abstract: The aim of this study is to evaluate the effect of rice, mung bean, and wheat noodle ingestion on intestinal gas production and postprandial gastrointestinal (GI) symptoms in non-constipation irritable bowel syndrome (IBS) patients. Methods: Twenty patients (13 F, 46 ± 11 y) underwent 8 h breath test studies and GI symptom evaluations after standard rice, wheat, or mung bean noodle meals at 8:00 a.m. in a randomized crossover study with a 1-week washout period. The same meal was ingested at 12:00 p.m. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…We performed breath test studies only after lunch because a previous study in our laboratory found that increased intestinal gas production by a high-FODMAP food item (wheat) had significant effects on H 2 and CH 4 concentrations in breath samples and GI symptoms after lunch but not after breakfast [20]. The limitations of this study and further study suggestions are as follows: (1) the study was not double-blinded, which may have led to some bias with symptom outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…We performed breath test studies only after lunch because a previous study in our laboratory found that increased intestinal gas production by a high-FODMAP food item (wheat) had significant effects on H 2 and CH 4 concentrations in breath samples and GI symptoms after lunch but not after breakfast [20]. The limitations of this study and further study suggestions are as follows: (1) the study was not double-blinded, which may have led to some bias with symptom outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Rice is absorbed in the small intestine and produces negligible amounts of intestinal gas [29]. Furthermore, cellophane noodles made from mung bean flour, a traditional Asian food, produce much less intestinal gas than do wheat noodles [30]. These main differences between the diet in Asia and Western countries might at least partially explain the differences mentioned above between patients with IBS in Asian and Western countries, including in its prevalence, sex difference, and clinical presentation.…”
Section: Role Of Diet In Ibsmentioning
confidence: 99%
“…Protein could be fermented to produce sulfur-containing and nitrogen-containing gases. A large amount of gas accumulated in enteric cavity and led to high intraluminal pressure, which then induced abdominal pain, abdominal discomfort, and other symptoms[ 36 , 37 ]. In addition, metabolic products of protein fermentation, such as short-chain fatty acids and phenolic and indolic compounds, exerted harm in the intestinal tract depending on the imbalance among the rates of production, absorption, and excretion[ 38 ].…”
Section: Discussionmentioning
confidence: 99%